A halogen-free high-gloss flame-retardant polystyrene material and its preparation method and application
By using low-melting glass powder in polystyrene materials with phosphorus- and nitrogen-based flame retardants, combined with toughening agents and polyolefin grafts, the problem of poor flame retardancy and gloss of existing polyphenylene ether/polystyrene alloy materials is solved, and a halogen-free polystyrene material with high flame retardancy and high gloss is achieved, which is suitable for a variety of electronic equipment.
Patent Information
- Application Number
- CN202111452437.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-01
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2041-12-01
AI Technical Summary
The existing polyphenylene ether/polystyrene alloy materials have poor flame retardancy and glossiness, which limits their application areas.
Halogen-free high-gloss flame-retardant polystyrene material is used to improve the flame retardancy and glossiness of the material by combining low-melting glass powder with phosphorus and nitrogen-based flame retardants.
It has achieved high flame retardancy of polystyrene materials, reaching V-0 or above, and significantly improving the gloss of the materials, and is suitable for household appliances, office supplies and other fields.
Smart Images

Figure BDA0003386689290000011 
Figure BDA0003386689290000031 
Figure BDA0003386689290000071
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of engineering plastics, and particularly relates to a halogen-free high-gloss flame-retardant polystyrene material and a preparation method and application thereof. Background Art
[0002] Polyphenylene ether (PPE) is a high-performance thermoplastic engineering plastic that is non-toxic, transparent, and has a low relative density. It has excellent mechanical strength, electrical properties, stress relaxation resistance, creep resistance, heat resistance, water resistance, water vapor resistance, and dimensional stability. However, its melt viscosity is high, its fluidity is poor, and it is difficult to process and shape, and it is difficult to use alone. At present, most PPE is formed by blending with polystyrene (PS) to form polyphenylene ether / polystyrene alloys, which can greatly improve processing performance, improve stress cracking resistance and impact performance, and significantly reduce costs. At the same time, it also has various excellent properties of PPE. It can also be flame-retardant by adding bromine-based, phosphorus-nitrogen-based and other flame retardants. It can be widely used in electrical appliances, automotive parts, office equipment, home appliances and other fields.
[0003] However, existing polyphenylene oxide / polystyrene alloy materials are basically compounded with high impact polystyrene (HIPS) PPE, and tougheners mostly use traditional styrene / butadiene / styrene block copolymers (SBS), styrene / isoprene / styrene block copolymers (SIS) and styrene / ethylene / butylene / styrene block copolymers (SEBS), etc., because the glossiness of HIPS and SBS is very poor, resulting in the poor appearance of the obtained alloy material, thereby limiting its application field. For example, Chinese patent CN107903608A discloses a halogen-free flame retardant and high temperature resistant polyphenylene oxide alloy material including polyphenylene oxide, polystyrene, toughener, compounded flame retardant, thermoplastic polyimide, compatibilizer, antioxidant, wherein the compounded flame retardant is composed of phosphorus flame retardant and nitrogen flame retardant, and the toughener is styrene-butadiene-styrene copolymer, etc., and the alloy material has high strength, high impact resistance, high temperature resistance, and excellent comprehensiveness of high flame retardancy, but the flame retardancy of the alloy material needs to be further improved, and the alloy material appearance is poor at the same time. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a halogen-free high-gloss flame-retardant polystyrene material and a preparation method and application thereof, so as to overcome the defects of the polyphenylene ether alloy material in the prior art in terms of poor flame retardancy and glossiness.
[0005] The present invention provides a halogen-free high-gloss flame-retardant polystyrene material, wherein the material components include, by weight:
[0006]
[0007]
[0008] The glass powder is a low-melting-point glass powder, and the melting temperature of the low-melting-point glass powder is 350-600° C.;
[0009] The toughening agent includes one or more of ABS grafted rubber powder, EPDM rubber, and acrylic resin.
[0010] Preferably, the polyphenylene ether resin includes one or more of poly (2,6-dimethyl-1,4-phenylene) ether, poly (2,6-diethyl-1,4-phenylene) ether, poly (2,6-dipropyl-1,4-phenylene) ether, poly (2-methyl-6-ethyl-1,4-phenylene) ether, poly (2-methyl-6-propyl-1,4-phenylene) ether, and 2,6-dimethylphenol / 2,3,6-trimethylphenol copolymer.
[0011] Preferably, the intrinsic viscosity of the polyphenylene ether resin is 35 to 45 cm 3 / g. The test standard of intrinsic viscosity is GB / T1632-1993 (30°C, chloroform solution).
[0012] Preferably, the polystyrene resin is a polymer synthesized from styrene monomers via free radical addition polymerization.
[0013] Preferably, the polystyrene resin has a melt flow rate of 6-10 g / 10 min at 200° C. / 5 kg. The test standard for melt flow rate is ISO 1133-1-2011.
[0014] Preferably, the phosphorus-based flame retardant includes one or more of triphenyl phosphate, bisphenol A-bis(diphenyl phosphate), resorcinol-bis(diphenyl phosphate), hydroquinone bis(diphenyl phosphate), and resorcinol bis[di(2,6-dimethylphenyl)phosphate].
[0015] Preferably, the nitrogen-based flame retardant includes one or more of tris(2-hydroxyethyl)isocyanurate, triglycidylisocyanurate, melamine cyanurate, melamine polyphosphate, dicyandiamide, ammonium polyphosphate, boric acid amine, and dicyandiamide formaldehyde resin.
[0016] Preferably, the particle size D50 of the low-melting-point glass powder is 0.5-7 μm.
[0017] Preferably, the average rubber particle size of the toughening agent is 250-500nm. In order to achieve a high gloss effect, a toughening agent with a reasonable rubber particle size must be selected. If the average particle size is less than 200nm, the toughening effect is not obvious, and if the average particle size is greater than 500nm, the gloss of the material will be seriously affected.
[0018] Preferably, the polyolefin graft comprises PP grafted with maleic anhydride; the grafting rate of maleic anhydride is 1-2%.
[0019] Preferably, the test method of the maleic anhydride grafting rate includes: heating the PP grafted maleic anhydride with xylene (analytical grade, commercially available) to reflux for 2h, pouring it into a beaker while hot, precipitating it with acetone (analytical grade, commercially available) after cooling, filtering it with suction, washing it with acetone twice and filtering it with suction, and finally drying it in a 90°C vacuum drying oven for 6h. The refined PP grafted maleic anhydride is placed in a 500ml conical flask, and xylene is poured in, refluxed for more than 20min until the grafted material is dissolved, and KOH / ethanol (KOH, analytical grade, commercially available; ethanol, analytical grade, commercially available) solution is added after cooling, and then heated and refluxed until the precipitate is dissolved. After cooling, phenolphthalein is used as an indicator (analytical grade, commercially available), and the unreacted KOH is titrated with acetic acid (analytical grade, commercially available) / xylene solution, and the amount of acid consumed is recorded. The grafting rate is calculated according to the following formula:
[0020]
[0021] G——grafting rate, %;
[0022] C1——concentration of KOH / ethanol standard solution, mol / L;
[0023] V1——the volume of excess KOH / ethanol standard solution added, ml;
[0024] C2——concentration of acetic acid / xylene solution, mol / L;
[0025] V2——The volume of acetic acid / xylene standard solution consumed during the titration, ml;
[0026] M is the mass of the refined sample of polyolefin grafted product, g.
[0027] Preferably, the weight portion of the polyphenylene ether resin is 28 to 35 parts; the weight portion of the polystyrene resin is 10 to 30 parts; the weight portion of the phosphorus-based flame retardant is 17 to 19 parts; the weight portion of the nitrogen-based flame retardant is 6 to 7 parts; the weight portion of the low-melting point glass powder is 2 to 3 parts; the weight portion of the toughening agent is 13 to 18 parts; and the weight portion of the polyolefin graft is 3 to 4 parts.
[0028] Preferably, the material further comprises 0 to 2 parts of a processing aid.
[0029] Preferably, the processing aid includes one or more of an anti-drip agent, an antioxidant, a lubricant, a weathering agent, and a colorant.
[0030] Preferably, the anti-dripping agent is present in an amount of 0.1 to 2 parts by weight.
[0031] Preferably, the anti-dripping agent includes one or more of polytetrafluoroethylene, styrene-acrylonitrile coated polytetrafluoroethylene, and acrylate coated polytetrafluoroethylene.
[0032] Preferably, the antioxidant is present in an amount of 0.1 to 1 part by weight.
[0033] Preferably, the antioxidant includes one or both of organic hindered phenol antioxidants and phosphite antioxidants.
[0034] Preferably, the organic hindered phenol antioxidant is antioxidant 1010 (pentaerythritol tetrakis[methyl-β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate]), and the phosphite antioxidant is antioxidant 168 (tris[2.4-di-tert-butylphenyl]phosphite).
[0035] Preferably, the lubricant is present in an amount of 0.1 to 2 parts by weight.
[0036] Preferably, the lubricant includes one or more of amide lubricants, stearate lubricants, ester lubricants, and silicone lubricants.
[0037] Preferably, the weight portion of the weathering agent is 0.1 to 2 parts.
[0038] Preferably, the weathering agent includes one or more of a benzophenone ultraviolet absorber, a benzotriazole ultraviolet absorber and a hindered amine light stabilizer.
[0039] Preferably, the colorant is present in an amount of 0.1 to 2 parts by weight.
[0040] Preferably, the colorant includes one or more of titanium dioxide, cadmium pigments, iron oxide red, ultramarine, carbon black, phthalocyanine and quinacridone organic pigments.
[0041] The present invention also provides a method for preparing a halogen-free high-gloss flame-retardant polystyrene material, comprising:
[0042] (1) mixing low melting point glass powder and silicone oil in a ratio of 0.8-1.5 g: 0.3-1.2 mL to obtain a low melting point glass powder mixture;
[0043] (2) Premix 27-38 parts of polyphenylene ether resin, 5-33 parts of polystyrene resin, 15-20 parts of phosphorus flame retardant, 5-8 parts of nitrogen flame retardant, 12-22 parts of toughening agent and 2-5 parts of polyolefin graft according to weight parts, add the obtained mixture into a twin-screw extruder, add the low-melting point glass powder mixture in step (1) into the twin-screw extruder, extrude and granulate to obtain a halogen-free high-gloss flame-retardant polystyrene material, wherein the weight part of the low-melting point glass powder is 1-5 parts.
[0044] Preferably, 0 to 2 parts of a processing aid are added during the premixing in step (2).
[0045] Preferably, in step (2), the premixing speed is 100 to 800 rpm, and the premixing time is 1 to 6 minutes.
[0046] Preferably, in step (2), the low melting point glass powder mixture is added into the twin-screw extruder in the fifth screw barrel.
[0047] Preferably, in step (2), the temperature of each screw section of the twin-screw extruder is 180-300° C., the aspect ratio is 30-45, and the screw speed is 200-500 rpm.
[0048] The present invention also provides an application of a halogen-free high-gloss flame-retardant polystyrene material in household appliances, office supplies or information and communication appliances, such as a television back shell, a refrigerator electric control box shell, a laser printer toner cartridge assembly and a display shell.
[0049] Beneficial Effects
[0050] The present invention adopts low melting point glass powder compounded with phosphorus flame retardant and nitrogen flame retardant, which synergistically makes the flame retardant effect of polystyrene material reach V-0 level or above, and the low melting point glass powder can significantly improve the glossiness of styrene material.
[0051] The present invention disperses low-melting-point glass powder in silicone oil in advance, and then adds the low-melting-point glass powder into the fifth screw barrel through a liquid filling pump, thereby strengthening the dispersion of the low-melting-point glass powder and improving the synergistic flame retardant effect and glossiness effect of the low-melting-point glass powder.
[0052] The polyolefin graft and the toughening agent in the present invention have a synergistic effect, thereby improving the toughness of the styrene material. DETAILED DESCRIPTION
[0053] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0054] Source of raw materials:
[0055] PPE LXR040: polyphenylene ether, intrinsic viscosity is about 38-42cm 3 / g, Nantong Xingchen Synthetic Materials Co., Ltd.;
[0056] PPE LXR050: polyphenylene ether, intrinsic viscosity 48-53cm 3 / g, Nantong Xingchen Synthetic Materials Co., Ltd.;
[0057] GP1441: polystyrene resin, melt flow rate 8g / 10min (200℃ / 5kg, ISO 1133-1-2011), Total;
[0058] GPPS-251: polystyrene resin, melt flow rate 2.4g / 10min (200℃ / 5kg, ISO 1133-1-2011), Shanghai Secco Petrochemical Co., Ltd.;
[0059] WSFR-BDP: bisphenol A-bis(diphenyl phosphate), Zhejiang Wansheng Co., Ltd.;
[0060] WSFR-RDP: resorcinol-bis(diphenyl phosphate), Zhejiang Wansheng Co., Ltd.;
[0061] FP-2200S: ammonium polyphosphate, Aidico Fine Chemicals (Shanghai) Co., Ltd.;
[0062] HT-211: melamine cyanurate, Shandong Taixing New Materials Co., Ltd.;
[0063] D250: low melting point glass powder, melting temperature 500°C, particle size D50 is about 6.5μm, Anmi Micro-Nano New Materials (Guangzhou) Co., Ltd.
[0064] GS-1500: low melting point glass powder, melting temperature 700℃, particle size D50 is about 6.5μm, Shanggao County Mingzheng Plastic Co., Ltd.
[0065] C4051: low melting point glass powder, melting temperature 500℃, particle size D50 about 7.5μm, Foshan Youhe Chemical Technology Co., Ltd.
[0066] ABS POW HR181: ABS grafted rubber powder, average rubber particle size is 320-350nm, Kumho Petrochemical Co., Ltd., South Korea;
[0067] ABS 60P: ABS grafted rubber powder, average rubber particle size is about 300nm, Guoqiao Petrochemical Co., Ltd.
[0068] E700N: EPDM rubber toughening agent, average rubber particle size is 350nm, Guangzhou Runfeng Chemical Co., Ltd.;
[0069] XC640: acrylic resin, average rubber particle size 380-440nm, Kumho Petrochemical Company, South Korea;
[0070] ABS PA-757K: ABS grafted rubber powder and AS resin blend (ABS resin), Zhenjiang Chimei Chemical Co., Ltd.
[0071] YH-792E: styrene / butadiene / styrene block copolymer, average rubber particle size is about 1 μm, Sinopec Baling Petrochemical Co., Ltd.;
[0072] PS 350K: high impact polystyrene, average rubber particle size 0.8-2μm, Guoqiao Petrochemical Co., Ltd.;
[0073] AP5000H: ABS grafted rubber powder, average rubber particle size is about 200nm, Thai Petrochemical Industry Company;
[0074] AP6007: ABS grafted rubber powder, average rubber particle size is about 800nm, Thai Petrochemical Industry Company;
[0075] CMG5701: PP grafted with maleic anhydride, the grafting rate of maleic anhydride is about 1.1%, Jiayirong Polymer (Shanghai) Co., Ltd.
[0076] CMG9801: PP grafted with maleic anhydride, the grafting rate of maleic anhydride is about 0.7%, Jiayirong Polymer (Shanghai) Co., Ltd.
[0077] PP-g-MAH-1020: PP grafted with maleic anhydride, the maleic anhydride grafting rate is about 2.3%, and it is homemade. The method is as follows: 100 parts by weight of polypropylene homopolymer (T30S, Fushun Ethylene Chemical Co., Ltd.), 3.5 parts by weight of maleic anhydride (maleic anhydride, Zibo Qixiang Tengda Chemical Co., Ltd.), 0.15 parts by weight of hindered phenol and phosphite antioxidants (antioxidant 1010 and antioxidant 168 mass ratio 1:2, commercially available) and a small amount of white oil are mixed evenly, and then added to a co-rotating twin-screw extruder with a length-to-diameter ratio of 52:1 through the main feeding port; a liquid composition containing 0.2 parts by weight of divinylbenzene (industrial grade, Wuhan Jixin Yibang Biotechnology Co., Ltd.), 0.11 parts by weight of dibenzoyl peroxide (industrial grade, Jiangsu Yuanyang Pharmaceutical Co., Ltd.) and a small amount of white oil is added to the extruder from the side feeding port of the third screw barrel. The temperature of the reaction extruder is adjusted to 190-230°C and the rotation speed is 100-400rpm, and the PP grafted maleic anhydride is obtained through traction, granulation and post-treatment processes; POLY TS 30X: styrene-acrylonitrile coated polytetrafluoroethylene anti-drip agent, Pacific International Chemical Co., Ltd. (PIC) of South Korea;
[0078] Antioxidant: antioxidant 1010, antioxidant 168, commercially available;
[0079] EBS: Ethylene bisstearamide lubricant, commercially available.
[0080] Preparation method of polystyrene materials in Examples 1-13, 15-17 and Comparative Examples 1-10:
[0081] (1) mixing low-melting-point glass powder and methyl silicone oil (201-10, Qingdao Zhongbao Silicon Material Technology Co., Ltd.) at a ratio of 1 g:0.6 mL to obtain a low-melting-point glass powder mixture;
[0082] (2) According to the formula of Table 1, Table 2 or Table 3, the other components except the low melting point glass powder are sequentially added into a mixer for premixing at a rotation speed of 100 to 800 rpm for a mixing time of 1 to 6 minutes, and then the mixture is conveyed to a twin-screw extruder through a plunger pump. The low melting point glass powder mixture in step (1) is added into the twin-screw extruder in the fifth screw barrel through a liquid adding pump. The temperature of each section of the screw of the extruder is controlled between 180 and 300° C., the aspect ratio of the twin-screw extruder is 30 to 45, and the screw speed is 200-500 rpm. Under the shearing, mixing and conveying of the screw, the materials are fully melted and compounded, and then extruded, granulated and dried to obtain a styrene material.
[0083] The components in Example 14 are prepared according to the above-mentioned method for preparing styrene materials. Instead of mixing methyl silicone oil with low-melting point glass powder, the low-melting point glass powder is directly added to the twin-screw extruder in the fifth screw barrel. The rest is the same as the above-mentioned preparation method to obtain a styrene material.
[0084] The styrene materials in the examples and comparative examples were first injection molded into standard test specimens according to standard sizes (the glossiness test was conducted using a 100*100*2.5 mm square plate), and then various performance tests were performed according to the following standards:
[0085] (1) Flame retardant grade test: thickness 2.0 mm, according to standard UL94-2018, the flame retardant grades from high to low are 5VA, V-0, V-1, V-2 and HB.
[0086] (2) Izod notched impact strength: in accordance with standard ISO 180-2000, test conditions are 23°C, A-notch.
[0087] (3) Gloss: According to ASTM D523-2018, the test condition is 60°.
[0088] Table 1 Example 1-11 ratio (weight parts)
[0089]
[0090] Table 2 Proportions of Examples 12-17 (parts by weight)
[0091]
[0092]
[0093] Table 3 Comparative proportions (parts by weight)
[0094]
[0095]
[0096] As shown in Tables 1-3, Comparative Example 3 does not add nitrogen flame retardant, Comparative Example 4 does not add phosphorus flame retardant, and Comparative Example 5 does not add low melting point glass powder. The flame retardancy of polystyrene materials in Comparative Examples 3-5 is significantly lower than that in Example 1. Comparative Example 6 uses ammonium polyphosphate flame retardant instead of phosphorus flame retardant and nitrogen flame retardant, and its polystyrene material has lower flame retardancy than Example 1. Comparative Example 10 uses glass powder with a melting temperature higher than 600°C, and its flame retardancy is lower than that in Example 1. It can be seen that the compounding of low melting point glass powder, phosphorus flame retardant and nitrogen flame retardant can synergistically improve the flame retardant effect, and the flame retardant effect reaches V-0 level or above, thereby meeting the needs of household appliance industries such as TV back shells and router shells, and office supplies industries such as optical printer front panels. Comparative Example 5 does not add low melting point glass powder, and the glossiness is significantly lower than that in Example 1, and the glossiness cannot reach above 70, which cannot meet the needs of household appliance industries such as TV back shells and router shells, and office supplies industries such as optical printer front panels.
[0097] In the preparation method of Example 14, the low melting point glass powder is not pre-dispersed in methyl silicone oil, and the flame retardancy and toughness of the prepared polystyrene material are lower than those of Example 1. It can be seen that methyl silicone oil can enhance the dispersion of low melting point glass, thereby improving the synergistic flame retardant effect and glossiness effect of the low melting point glass powder.
[0098] Comparative Example 1 does not add PP grafted maleic anhydride, and Comparative Example 2 does not add a toughening agent. The Izod notched impact strength of the polystyrene materials in Comparative Examples 1 and 2 is significantly lower than that in Example 1. It can be seen that the combination of PP grafted maleic anhydride and a toughening agent synergistically increases the toughness of the styrene material, and the Izod notched impact strength reaches 7.0 kJ / m 2 The above can meet the needs of home appliance industry such as TV back shell, router shell and office supplies industry such as optical printer front panel.
[0099] Comparative Example 7 uses general ABS resin for toughening, and Comparative Examples 8 and 9 use conventional toughening agents. The toughness of the polystyrene material is very poor and the glossiness is also average. The reason may be that the general ABS has poor compatibility with the substrate resin.
Claims
1. A halogen-free high-gloss flame-retardant polystyrene material, characterized in that: The material components include by weight: 27-38 parts of polyphenylene ether resin; 5-33 parts of polystyrene resin; 15-20 parts of phosphorus flame retardant; 5-8 parts of nitrogen flame retardant; 1~5 parts of glass powder; 12-22 parts of toughening agent; 2-5 parts of polyolefin grafted material; The glass powder is a low-melting-point glass powder, and the melting temperature of the low-melting-point glass powder is 350-600° C.; The toughening agent includes one or more of ABS grafted rubber powder, EPDM rubber, and acrylic resin, wherein the average rubber particle size of the toughening agent is 250-500 nm; the melt flow rate of the polystyrene resin at 200°C / 5kg is 6-10g / 10min; The phosphorus-based flame retardant includes one or more of triphenyl phosphate, bisphenol A-bis(diphenyl phosphate), resorcinol-bis(diphenyl phosphate), hydroquinone bis(diphenyl phosphate), and resorcinol bis[di(2,6-dimethylphenyl) phosphate]; the nitrogen-based flame retardant includes one or more of tris(2-hydroxyethyl)isocyanurate, triglycidylisocyanurate, melamine cyanurate, melamine polyphosphate, dicyandiamide, ammonium polyphosphate, boric acid amine, and dicyandiamide formaldehyde resin.
2. The polystyrene material according to claim 1, characterized in that The polyphenylene ether resin includes one or more of poly (2,6-dimethyl-1,4-phenylene) ether, poly (2,6-diethyl-1,4-phenylene) ether, poly (2,6-dipropyl-1,4-phenylene) ether, poly (2-methyl-6-ethyl-1,4-phenylene) ether, poly (2-methyl-6-propyl-1,4-phenylene) ether, and 2,6-dimethylphenol / 2,3,6-trimethylphenol copolymer; the intrinsic viscosity of the polyphenylene ether resin is 35-45 cm 3 / g.
3. The polystyrene material according to claim 1, characterized in that: The particle size D50 of the low melting point glass powder is 0.5-7 μm.
4. The polystyrene material according to claim 1, characterized in that: The polyolefin grafted material comprises PP grafted with maleic anhydride; the grafting rate of the maleic anhydride is 1-2%.
5. The polystyrene material according to claim 1, characterized in that The weight portion of the polyphenylene ether resin is 28 to 35 parts; the weight portion of the polystyrene resin is 10 to 30 parts; the weight portion of the phosphorus flame retardant is 17 to 19 parts; the weight portion of the nitrogen flame retardant is 6 to 7 parts; the weight portion of the low-melting point glass powder is 2 to 3 parts; the weight portion of the toughening agent is 13 to 18 parts; and the weight portion of the polyolefin graft is 3 to 4 parts.
6. The polystyrene material according to claim 1, characterized in that: The material also includes 0-2 parts of processing aids; the processing aids include one or more of an anti-dripping agent, a lubricant, a weathering agent, and a colorant.
7. The polystyrene material according to claim 6, characterized in that: The weathering agent includes an antioxidant.
8. A method for preparing the halogen-free high-gloss flame-retardant polystyrene material according to any one of claims 1 to 4, comprising: (1) mixing low melting point glass powder and silicone oil in a ratio of 0.8-1.5 g: 0.3-1.2 mL to obtain a low melting point glass powder mixture; (2) Premix 27-38 parts of polyphenylene ether resin, 5-33 parts of polystyrene resin, 15-20 parts of phosphorus flame retardant, 5-8 parts of nitrogen flame retardant, 12-22 parts of toughening agent and 2-5 parts of polyolefin graft according to parts by weight, and add the obtained mixture to a twin-screw extruder. Add the low-melting point glass powder mixture in step (1) to the twin-screw extruder, extrude and granulate to obtain a halogen-free high-gloss flame-retardant polystyrene material, wherein the weight portion of the low-melting point glass powder is 1-5 parts.
9. The preparation method according to claim 8, characterized in that In the step (2), 0-2 parts of processing aid are added during premixing; the low melting point glass powder mixture is added to the twin-screw extruder in the fifth screw barrel; the screw temperature of each section of the twin-screw extruder is 180-300°C, the aspect ratio is 30-45, and the screw speed is 200-500 rpm.
10. Use of the polystyrene material according to any one of claims 1 to 5 in household appliances, office supplies or information and communication appliances.
Citation Information
Patent Citations
Halogen-free flame-retardant high-temperature-resistant polyphenyl ether alloy material and preparation method thereof
CN107903608A
Inflaming retarding PPE / PS / ABS alloy plastic as well as preparation method and application thereof
CN103467966A
High-gloss polypropylene microcellular material and production method thereof
CN110452465A
5VA-grade halogen-free flame-retardant polypropylene material and preparation method thereof
CN112321947A
Halogen-free flame-retardant ABS alloy material and preparation method thereof
CN113248901A